(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the study, a control group consisting of 10 women without eclampsia, 13 women with moderate eclampsia, and 13 women with severe eclampsia participated. The course of pregnancy and features of the delivery process were examined, and the pathological examination of the placentas was conducted. It was found that severe eclampsia is associated with a high incidence of chronic placental insufficiency, subcompensated and decompensated processes, early childbirth, and increased rates of perinatal diseases and mortality. The identified relationships between the pathological parameters of the placenta and obstetric complications indicate the presence of similar mechanisms for the development of these obstetric complications. The study aimed to investigate the pathological characteristics of the placenta in cases of eclampsia.